ترجمة معاني القرآن الكريم بالكلمات العربية المستعملة في اللغة الأمّ ترجمة سورة الفاتحة باللغة البنغالية نموذجا - Mohammad Hafizullah; Zainal Abidin Hajib; Zainur Rijal Abdul Razak (USIM Press, 2024)
Vol. 1 No. 2 (2022)